Upaya Penurunan Frekuensi Non-Conformity Notification (NCN) untuk Mengurangi Proses Rework pada Departemen IMM di PT. X - Florian Kevin Verandi; Karina Agustin (Jurnal Titra, 2023)
PT. X manufactures plastic packaging for cosmetics such as compacts, lipstick, bottles, and jars. PT. X wants to reduce the frequency of Non-Conformity Notification (NCN) discoveries, which are the products that do not meet the product quality standard after being sorted by operators. The highest frequency of NCN occurred in the Injection Molding Machine (IMM) production department, with the top types of NCN being ex-treatment, flashing, and dirty oil. The method used in this research is DMAIC, and the tool used to analyze the causes of the problem is the five whys analysis. From the analysis results, the cause of NCN ex-treatment is the location of the packing basket, which prevents operators from using the blower. The causes of NCN Flashing are the machine’s parameters and worn-out mold. The causes of NCN dirty oil are products touching the mold pin, oil dripping into the product bin, and limited spare gloves. The proposed improvement for ex-treatment is rearranging the layout of the work area. Proposals for flashing are to make standard parameters and repair mold. The suggestions for dirty oil are widening the machine’s opening, cleaning the dropping bin every shift change, and providing new gloves or oil wipes.